2012
DOI: 10.1007/s12663-012-0383-5
|View full text |Cite
|
Sign up to set email alerts
|

Mantle Cell Lymphoma of the Oral Cavity with Multiple Foci: A Case Report and Review of the Literature

Abstract: Non-Hodgkin lymphomas (NHLs) are often present outside the lymph nodes. Although primary extranodal NHLs form a substantial part of all NHLs, reports on oral primary extra nodal NHLs are rare. Mantle cell lymphoma (MCL) is a rare B-cell neoplasm that has only recently been defined as a distinct entity. MCL of the oral cavity is an uncommon diagnosis. Most oral MCLs occur in an elderly male population and have a possible predilection for the palate. The microscopic diagnosis can be challenging, given its simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
2
0
4
Order By: Relevance
“…As noted above, translocations that juxtapose CCND1 with the IGH locus [t(11;14)(q13;q32)] are a genetic hallmark of MCL, and cyclin D1 overexpression via this mechanism is present in virtually all (>90%) cases of MCL (Bertoni et al , ). To date, ten cases of oral cavity MCL have been reported (Rajkumar et al , ), less than half with a cytogenetic analysis, which always confirmed translocation (Guggisberg and Jordan, ; Kyo et al , ; Scheller et al , ; Table ). In the largest cohort of oral cavity, plasmablastic lymphoma (PBL) patients published to date Boy et al () evaluated t(11;14)(q13;q32) and obtained a positive t(11;14)(q13;q32) result in only 1 of 41 cases (2.4%); they observed an increased number of CCND1 copies in 17 of these cases (41.4%), of which 7 (17%) were amplifications.…”
Section: Diagnostic and Prognostic Implications Of Cyclin D1 In Oral mentioning
confidence: 99%
“…As noted above, translocations that juxtapose CCND1 with the IGH locus [t(11;14)(q13;q32)] are a genetic hallmark of MCL, and cyclin D1 overexpression via this mechanism is present in virtually all (>90%) cases of MCL (Bertoni et al , ). To date, ten cases of oral cavity MCL have been reported (Rajkumar et al , ), less than half with a cytogenetic analysis, which always confirmed translocation (Guggisberg and Jordan, ; Kyo et al , ; Scheller et al , ; Table ). In the largest cohort of oral cavity, plasmablastic lymphoma (PBL) patients published to date Boy et al () evaluated t(11;14)(q13;q32) and obtained a positive t(11;14)(q13;q32) result in only 1 of 41 cases (2.4%); they observed an increased number of CCND1 copies in 17 of these cases (41.4%), of which 7 (17%) were amplifications.…”
Section: Diagnostic and Prognostic Implications Of Cyclin D1 In Oral mentioning
confidence: 99%
“…A idade média de incidência é de 60 anos e existe um predomínio dos homens sobre as mulheres (2:1). 35,[37][38][68][69] De acordo com a Organização mundial da saúde (OMS), são reconhecidos dois tipos clínicos, devido ao desenvolvimento da neoplasia de maneiras diferente 19 (Quadro 2.9). Além disso, o LCM pode mostrar histologicamente uma proliferação de células monomórficas dispostas de maneira difusa, vagamente nodular ou padrão da zona do manto.…”
Section: Linfomas De Células Do Mantounclassified
“…Também podem estar presentes histiócitos e vasos hialinizados e/ou epitelioides histiocitos, que é uma pista diagnóstica importante. [36][37][38]42,67,68…”
Section: Linfomas De Células Do Mantounclassified
See 2 more Smart Citations